China and the World Trade Organization : a Legal Perspective. - Qingjiang, Kong (World Scientific Publishing Company, 2002)
This book examines, from the legal perspective, China's process of WTO accession, its commitments to the accession, the implications of such commitments for its trade and legal systems, and its efforts toward WTO compliance. It also discusses the issue of the capacity of the evolving Chinese legal system for ensuring compliance. In particular, the book probes into the trade and legal systems at the turn of the accession and evaluates selected trade and legal issues, including intellectual property, foreign investment law and settlement of trade disputes. Contents: China and the WTO Law: China'